Analysis and improvement of human stability in floodwaters through numerical simulation with SPH-DEM model - Zhang, Lifang; Zhang, Jianmin (Journal of hydraulic research, 2025)
This study improves the formulae for determining the incipient velocity of sliding and toppling instability through force analysis. It introduces a self-adjusting posture parameter to make the approach applicable to actual human subjects. In addition, a novel concept of critical water depth is proposed to classify the type of instability. The smoothed particle hydrodynamics model, coupled with the discrete element method, is employed to simulate the instability scenarios of human bodies. Through the validated fluid-structure interaction model, the influence of critical factors on human stability is investigated, including the friction coefficient, height, mass, and body postures. The developed formulae are corroborated with experimental data about actual human subjects. The incipient velocity formula for toppling instability in a bending posture is introduced, previously overlooked in the literature. The results contribute new insights into the instability criterion for individuals in floodwaters and offer additional strategies to enhance human stability.